A New Method for Modulation, Control and Power Boosting in Microbial Fuel Cells. Issue 5 (13th June 2018) - Ieropoulos, I. A.; You, J.; Gajda, I.; Greenman, J.
Abstract: Microbial fuel cells (MFCs) are energy transducers, which through the metabolic reactions of facultative anaerobic microorganisms, transform the energy in organic matter directly into electricity. Extrinsic parameters such as hydraulic retention time, fuel quality (type and concentration) and physicochemical environment of electrodes and biofilms (e.g., temperature, pH, salinity, and redox), can all influence system efficiency. This work proposes that MFCs can be "fine‐tuned" by adjustment of any of the physicochemical conditions including redox potential; in this context, an entirely novel method was investigated as a practical means of tuning, modulating and monitoring the redox potential within the electrode chambers. The method uses additional electrodes – known as 3 rd and 4 th ‐pins for anode and cathode chambers, respectively – which can be used in individual units, modules, cascades or stacks, for optimising the production of a large variety of chemicals, as well as biomass, water and power. The results have shown that the power output modulation resulted in an up to 79% and 33% increase, when connected via 3 rd and 4 th pins, respectively. Apart from power improvement, this study also demonstrated a method of open circuit potential (OCP) sensing, by using the same additional electrodes to both monitor and control the MFC signal in real time.